CYTOTOXICITY IDENTIFICATION OF THE SUPERNATANT OF Manihot esculenta Crantz RHIZOME AS RIBOSOME-INACTIVATING PROTEIN TO NORMAL CELL - Endang Astuti; Sabirin Matsjeh; Winarto Haryadi; Deni Pranowo; Nuning Sri Mulatsih (Universitas Gadjah Mada, 2004)
The supernatant of Manihot esculenta Crantz rhizome has been used as an alternative remedy of infectious and cancer in Jogjakarta. Cytotoxicity assay showed that Manihot esculenta Crantz supernatant had cytotoxic effect to cancer cell line, namely Myeloma (LC50 = 180,24 μg/mL) and HeLa (LC50 = 415,55 μg/mL), but have a little cytotoxic effect to SiHa. This research was aimed to identify cytotoxic activity of Manihot esculenta Crantz's supernatant to normal cell, particularly to human mononuclear cell and Vero cell line, and to compare to the cancer cell lines. The result showed that supernatant of M. esculenta had cytotoxic effect to normal mononuclear cell (LC50 = 564,00 μg/mL) and Vero cell line (LC50 = 686,00 μg/mL). The supernatant of M. esculenta had the highest cytotoxic activity to myeloma and relatively toxic to cervix cancer HeLa and normal cell, but less to SiHa.